2022
DOI: 10.1002/jia2.26019
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider perceptions of a community‐based accompaniment intervention for adolescents transitioning to adult HIV care in urban Peru: a qualitative analysis

Abstract: Introduction Adolescents living with HIV (ALWH) experience higher mortality rates compared to other age groups, exacerbated by the suboptimal transition from paediatric to adult HIV care, during which decreased adherence to antiretroviral therapy (ART) and unsuppressed viremia are frequent. Care transition—a process lasting months or years—ideally prepares ALWH for adult care and can be improved by interventions that are youth‐friendly and address psychosocial issues affecting ART adherence; howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Adolescents who have family challenges and/or lack sufficient support from family and friends may benefit from peer accompaniment–a strategy that is effective for improving adolescent adherence to treatment for other diseases, including HIV and diabetes [ 29 , 30 ]. A pilot study conducted in Lima demonstrated the acceptability and feasibility of in-person peer support groups and group video-DOT (i.e., multiple adolescents taking their treatment together over a group video call) for adolescents living with HIV [ 31 , 32 ]. Notably, video-DOT for TB treatment is accepted by the WHO and the U.S. Centers for Disease Control and Prevention as a treatment delivery strategy because it achieves treatment outcomes that are at least as effective as conventional DOT, though these effectiveness data come mostly from high-income settings [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who have family challenges and/or lack sufficient support from family and friends may benefit from peer accompaniment–a strategy that is effective for improving adolescent adherence to treatment for other diseases, including HIV and diabetes [ 29 , 30 ]. A pilot study conducted in Lima demonstrated the acceptability and feasibility of in-person peer support groups and group video-DOT (i.e., multiple adolescents taking their treatment together over a group video call) for adolescents living with HIV [ 31 , 32 ]. Notably, video-DOT for TB treatment is accepted by the WHO and the U.S. Centers for Disease Control and Prevention as a treatment delivery strategy because it achieves treatment outcomes that are at least as effective as conventional DOT, though these effectiveness data come mostly from high-income settings [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Varios programas de navegación se han aplicado en algunos países latinoamericanos para mejorar la vinculación a la atención. En Perú, los resultados de una intervención piloto de nueve meses, con varios componentes a nivel individual y grupal que contemplaban navegación implementada por trabajadores de salud comunitarios realizada a partir del 2019, demostraron una alta aceptabilidad entre adolescentes (de 18 a 21 años que incluían HSH y MT) con VIH y el personal de salud (14) ; así como también su factibilidad y evidencia de mejora en la adherencia, apoyo social y autoeficacia en dichos usuarios adolescentes (15) . Participantes HSH y MT en un estudio en Guatemala fueron vinculados a la atención en una media de tres días y expresaron que el apoyo emocional de un navegador les ayudó a afrontar el temor frente a su diagnóstico (16) .…”
Section: Introductionunclassified